MODELING EFFECTIVE PRESENTATION COMMUNICATION SKILLS FOR ENGLISH EDUCATION STUDENTS - Wina Anjelina Harefa; Silvan Herniyanti Telaumbanua; Jacqueline Laoli; Selvin Try Hartati Harefa; Nurmawati Harefa; Agnes Fristaniat Zendrato; Yaredi Waruwu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Effective presentation communication skills are essential for English education students, as they play a significant role in academic success and professional development. This study explores key components that contribute to effective presentation skills, including confidence in speaking, clear and effective use of English, good pronunciation and intonation, logical responses to questions, audience interaction, and the use of technology. Using a qualitative research approach, in-depth interviews were conducted with 20 English education students at the University of Nias. The findings highlight the challenges students face, such as nervousness, language difficulties, and limited audience engagement strategies. The results suggest that practicing regularly, receiving feedback, watching professional presentation videos, joining public speaking clubs, using voice/video recordings, and improving vocabulary through daily conversations are effective strategies for enhancing presentation skills. These findings provide valuable insights for curriculum development and future training programs aimed at equipping students with the necessary skills to deliver impactful presentations. Future research can explore the impact of specific teaching methodologies on students’ presentation effectiveness.